O imperativo da cultura surda no plano conceitual: emergência, preservação e estratégias nos enunciados discursivos - Gomes, Anie Pereira Goularte (2011)
This work has considered the centrality of language in order to understand how the processes of conceptualization of the term deaf culture have been constituted, as this concept has acquired a status of truth and reality that has become increasingly stronger in the academic environment. The text presents a kind of research that problematizes utterances that constitute a discursive web about deaf culture. The focus is on analyzing how deaf culture has been narrated and thought by the deaf themselves and how it has been constituted as a concept, thus acquiring a real meaning and having a fundamental role in the constitution of the deaf subject, despite acting as a closed, universal concept. The subjected knowledges of the deaf community, as a way of enunciation of this cultural discourse, have triggered the analysis. Under this blend of truths that have been socially authorized by the deaf, deaf culture has become a conceptual imperative, thus inviting us to perceive those enunciations, as well as reflect and act on them. This concept has become a device that triggers discursive practices related to deafness. This work aims at perceiving the imperative of deaf culture at the conceptual level and seeks to genealogically understand the emergence of such a theme, the truths that have supported it and the discursive strategies involved in this process.